2015
DOI: 10.11648/j.sjph.20150302.19
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Long Lasting Insecticidal Nets Among Household in Malarious Areas of Raya Alamata District, Tigray, Ethiopia

Abstract: Abstract:Background: Malaria in Ethiopia is one of the most important public health problems, with more than threequarters of the landmass of the country and an estimated 68% of the total population is considered at risk of malaria infections. In the fight against this deadly disease, the country has deployed a massive amount of long lasting Insecticidal treated nets. Though this tremendous effort is outstanding, the distribution alone does not ensure the protection of the people from malaria. Thus, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…According to the finding of this study, being female was identified as predictor of ITN utilization. This finding is consistent with study conducted in Addis Zemen Hospital northern, Ethiopia, 36 Raya Alamata districts of Ethiopia, 21 and Arbaminch, Ethiopia 18 that found that females were less likely to utilize ITN than males. This might be also due to sociocultural background in which men are given priority over women in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the finding of this study, being female was identified as predictor of ITN utilization. This finding is consistent with study conducted in Addis Zemen Hospital northern, Ethiopia, 36 Raya Alamata districts of Ethiopia, 21 and Arbaminch, Ethiopia 18 that found that females were less likely to utilize ITN than males. This might be also due to sociocultural background in which men are given priority over women in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…The finding of this study indicated that 72.2% of households utilized ITN the night before the data collection day. This finding is consistent with results from Arbaminch town in southern Ethiopia (71%), 18 Alamata district in northern Ethiopia (73%), 21 Harari regional state, Ethiopia (73.3%), 22 Burkina Faso (70%), 14 and Nigeria (75.4%). 13 This is because all of the above studies including this study were conducted at malaria endemic area which might enforced the households to use ITNs due to the fear of malarial infection.…”
Section: Discussionsupporting
confidence: 90%
“…Similarily LLIN utilization was reported to be 73.3% in another a study done in Harari, Ethiopia which was also parallel to this study finding [17]. Also the study done among households in Raya Alamata District, Tigray Ethiopia 68.6% of them were utilized the LLIN [18] which is slightly lessthan this finging. A population-based survey done in southern Ethiopia showed that, from the total households participated in the study 61.1% had owned at least one LLIN.…”
Section: Discussionsupporting
confidence: 85%
“…The finding was in line with slight difference with the study from Southern Ethiopia, which was 27.2% (15). However, it was boldly lower than a study conducted in malaria endemic areas of Raya Alamata District, Ethiopia 71% and in Burkina Faso, 70% (13, 22). The possible explanation for such discrepancies could be geographical variations, the time gap between distributions of ITNs, and survey period and also other age groups might be utilized as evidenced in these studies (6).…”
Section: Discussionmentioning
confidence: 57%
“…According to this report, ITNs ownership and utilization of under-5 years old children in Southern, Nation, Nationalities and Peoples Region (SNNPR) of Ethiopia was 57 and 42%, respectively (4). According to studies conducted in different areas of Ethiopia, household ownership of at least one ITNs and ITNs utilization among under-5 years old children were 25.3 and 63.9%, respectively, at Adami Tulu district of Oromia region (9), 62.4 and 21.5%, respectively, at Gursum district of Oromia region (10), 95.8 and 59.1%, respectively, in Dejen Woreda, Amhara region (11), 98.4 and 69%, respectively, in Arbaminch Zuria woreda of SNNPR (6), 44.96 and 32% respectively, Shebedino district, SNNPR (12), 71.64% of utilization, Raya Alamata District of Amhara region (13), ownership was 56.6% in Gilgel-Gibe, Ethiopia (14), in SNNPR, 67.5% of households had used a bed net during the previous night. But, only 9.4% were used by children alone (15).…”
Section: Introductionmentioning
confidence: 99%